Odpowiedź:
zad 1
8 - 2x = 3(5 -x)
8 - 2x = 15 - 3x
- 2x + 3x = 15 - 8
x = 7
Odp: B
zad 2
x² + 2x - 15 = 0
a = 1 , b = 2 , c = - 15
Δ = b² - 4ac = 2² - 4 * 1 * (- 15) = 4 + 60 = 64
√Δ = √64 = 8
x₁ = ( - b - √Δ)/2a = (- 2 - 8)/2 = - 10/2 = - 5
x₂ = (- b + √Δ)/2a = (- 2 + 8)/2 = 6/2 = 3
Odp: A i C
zad 3
4α - jeden kat
α - drugi kąt
4α + 27° - trzeci kąt
4α + α + 4α + 27° = 180°
9α + 27° = 180°
zad 4
3(x - 1) - 4(x - 2) = 2(x - 3)
3x - 3 - 4x + 8 = 2x - 6
- x + 5 = 2x - 6
- x - 3x = - 6 - 5
- 4x = - 11
4x = 11
x = 11/4 = 2 3/4
zad 5
1 - (x + 1)/3 = x/2 | * 6
6 - 2(x + 1) = 3x
6 - 2x - 2 = 3x
- 2x + 4 = 3x
- 2x - 3x = - 4
- 5x = - 4
5x = 4
x = 4/5